Um ambiente computacional para emular em rede aplicações interativas desenvolvidas para televisão digital - Campana, Edriano Carlos [UNESP] (2015)
The objective of this work is to develop an inexpensive computational environment to emulate interactive applications for Digital Television. Such ans environment is established through a learning environment and research based on a local area network that emulates the environment offered by the Digital Television. This way, researchers, professionals and others interested in the paradigms offered by digital transmission may develop, research and study interactive mechanisms in a similar, accessible and inexpensive envinronment